Black-Tailed Prairie Dogs, Cattle, and the Conservation of North America’s Arid Grasslands - Sierra–Corona, Rodrigo (PLoS One, 2015)
Prairie dogs (Cynomys spp.) have been eliminated from over 95% of their historic range in large part from direct eradication campaigns to reduce their purported competition with cattle for forage. Despite the longstanding importance of this issue to grassland management and conservation, the ecological interactions between cattle and prairie dogs have not been well examined. We address this issue through two complementary experiments to determine if cattle and prairie dogs form a mutualistic grazing association similar to that between prairie dogs and American bison. Our experimental results show that cattle preferentially graze along prairie dog colony edges and use their colony centers for resting, resembling the mutualistic relationship prairie dogs have with American bison. Our results also show that prairie dog colonies are not only an important component of the grassland mosaic for maintaining biodiversity, but also provide benefits to cattle, thereby challenging the long-standing view of prairie dogs as an undesirable pest species in grasslands.